Repellent Potency of N-Hexane Extract Leaf and Stem Ocimum basilicum against Culex quinquefasciatus - Indri Ramayanti; Miranti Dwi Hartanti; Reynaldi Aulia Rahman (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2022)
The Culex quinquefasciatus mosquito is the main vector of filariasis, various ways to control vector breeding is the use of insecticide from natural ingredients, one of which is basil containing essential oils and proven is effective as a repellent against the mosquito. The objective of this research was to determine the repellent potency of n-hexane extract of basil leaves and stems against the Culex quinquefasciatus. This study was a laboratory experimental study using a completely randomized design, with 3 replications at 7 times intervals. The extract concentrations were 15%, 25%, 35 % and ethanol negative control 96%, the positive control repellent X containing 13% DEET. The results showed that the n-hexane extracts of basil leaves and stems for 6 hours at all concentrations were able to repel mosquitoes up to 92.51%, the one-way ANOVA analysis showed that the value of p= 0.000 (< 0.05), meaning that there was a difference in the number of C. quinquefasciatus perching on the black cloth at various concentrations of n-hexane extracts of leaves and stems of basil, while the probit analysis showed that the effective extract concentration at 90% was 31.52%. The extract of n-hexane leaves and basil stems was effective as a repellent against the C. quinquefasciatus.